Marketing performance measurement: marketing metrics in Turkish firms - Hacioglu, Gungor; Gök, Osman (Journal of Business Economics and Management, 2013)
This study explores which metrics are considered important in measuring marketing performance in Turkish firms. In addition, the study examines the effects of sectoral differences and market dynamism, and the relationship between the importance attached to metrics and firm performance. The data collected from a sample of 145 Turkish firms via a structured questionnaire derived from the literature reveals that the most importance is attached to consumers’ attitudes metrics. Economic value added and customer lifetime value are the least important metrics in performance evaluation. No significant relationship occurs between the importance that executives attach to metrics and firm performance. Managerial implications and future research opportunities will be presented at the end. The study is, as far as is known, the first attempt at aiming to explore marketing metrics in Turkey, and one of a limited number of studies in emerging economies.